2018
DOI: 10.1101/444919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pupillary dilations of mice performing a vibrotactile discrimination task reflect task engagement and response confidence

Abstract: Pupillometry, the measure of pupil size and reactivity, has been widely used to assess cognitive processes. As such, changes in pupil size have been shown to correlate with arousal, locomotion, cortical state and decision-making processes. In addition, pupillary responses have been linked to the activity of neuromodulatory systems that modulate attention and perception as the noradrenergic and cholinergic systems. Due to the extent of processes reflected by the pupil, we aimed at resolving pupillary responses … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Task performance is higher during immobile, quiet behavior with high arousal than during lower level of arousal or high motor activity (McGinley et al, 2015b; de Gee et al, 2018; Neske and McCormick, 2018; van Kempen et al, 2018). These changes in brain state can occur spontaneously during the task or reflect overall changes in task engagement (Ganea et al, 2018; Jacobs et al, 2018), Moreover, they are well correlated to pupil size and could relate partly to fluctuations in the activity of locus coeruleus noradrenergic neurons in the brainstem (de Gee et al, 2017, 2018).…”
Section: Impact Of Cortical States On Sensory Processingmentioning
confidence: 99%
“…Task performance is higher during immobile, quiet behavior with high arousal than during lower level of arousal or high motor activity (McGinley et al, 2015b; de Gee et al, 2018; Neske and McCormick, 2018; van Kempen et al, 2018). These changes in brain state can occur spontaneously during the task or reflect overall changes in task engagement (Ganea et al, 2018; Jacobs et al, 2018), Moreover, they are well correlated to pupil size and could relate partly to fluctuations in the activity of locus coeruleus noradrenergic neurons in the brainstem (de Gee et al, 2017, 2018).…”
Section: Impact Of Cortical States On Sensory Processingmentioning
confidence: 99%
“…In macaque monkeys, attention to the fingertips has been shown to increase the firing rate of neurons with corresponding receptive fields in the primary somatosensory cortex (Iriki et al, 1996). In rodents, pupil diameter was shown to be increased when rats were in a high behavioural state, defined by enhanced somatosensory detection, increased sensory evoked responses and lower population variability in the somatosensory cortex (Ganea et al, 2020; Lee & Margolis, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Locomotion and pupil diameter can be considered behavioral indications of engagement with the environment (Jacobs et al, 2018;Ganea et al, 2018;Bennett et al, 2013) and modulate neuronal activity in visual cortex (Dadarlat & Stryker, 2017;McGinley, David, et al, 2015;McGinley, Vinck, et al, 2015;Niell & Stryker, 2010;Polack et al, 2013;Reimer et al, 2014;Salkoff et al, 2020;Vinck et al, 2015). We found that in L2…”
Section: V1mentioning
confidence: 74%